Reconciling Islam and Human Rights: A Narrative Review of Reform, Resistance, and Realignment - Pramasto, Arafah (Yayasan Sinergi Kawula Muda, 2024)
The intersection of Islam and human rights has become an increasingly contested and vital area of academic inquiry. This narrative review aims to critically examine how Islamic jurisprudence interacts with international human rights principles, particularly in Muslim-majority societies. Using a multidisciplinary methodology, literature was collected from major academic databases including Scopus, Google Scholar, JSTOR, PubMed, and Web of Science. Keywords such as